Relationship Marketing in China: Guanxi, Favouritism and Adaptation - Wong, Y. H. (Journal of business ethics, 1999)
One of the hot research topics today is relationship marketing. However, little research has been carried out in understanding the complex concepts of Guanxi (relationship) in a Chinese society. This research describes a study to operate the constructs of guanxi and explores the importance of guanxi in relationship development in order to present a new Guanxi framework. A study of both Western and Chinese literature provides foundations of the Guanxi perspectives. The constructs of adaptation, trust, opportunism and favour are identified. Adaptation and trust are found to be positively correlated with sales stability and quality. Whilst, adaptation is negatively correlated with relationship termination costs. Both theoretical framework (a new perceptual map) and managerial implications are given. In addition, recommendations for future research are made.